Pengembangan E-LKPD Materi Sistem Peredaran Darah Dengan Google Site Untuk Siswa Kelas VIII.: (Development of E-LKPD Material on the Circulatory System Using Google Site for Class VIII Students) - Septiani , Septiani; Sari, Tika Mayang (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
The purpose of this study is to develop e-LKPD products using Google Sites, In this study the problem is the lack of variation in the way teachers teach. In this research using the ADDIE development method which has 5 stages of development, namely Analyse (analysis), Design (design), Development (development), Implementation, and Evaluation. With the subject of grade VIII students of SMP Negeri 1 Way Jepara who have received circulatory system material. Based on research that has been validated by material and media experts by getting a final score of material expert validation of 78% with the category of